2020
DOI: 10.1002/jemt.23610
|View full text |Cite
|
Sign up to set email alerts
|

The structural and ultrastructural organization of the cellular constituents of the trunk kidney of grass carp (Ctenopharyngodon idella)

Abstract: The trunk kidney of grass carp mainly consisted of renal tubules with a few interstitial hematopoietic tissues. The component structure of fish nephron markedly varies between different species of fish. The nephron of grass carp consisted of morphologically distinct segments; renal corpuscles, neck segment, proximal, intermediate, distal, and collecting tubules. The glomerulus of renal corpuscles mainly composed of mesangial cells and well‐developed podocytes that extended their processes to the endothelium of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Histological analysis has shown that the bichir renal corpuscle has the same structure as both lungfish and freshwater teleosts and amphibians [ 12 , 13 , 14 , 15 ]. It has been established that the cut diameter of the renal corpuscle increases in the series P. senegalus —freshwater bony fish Ctenopharyngodon idella ; Channa punctatus —amphibians Rana cancrivora; Triturus (Cynops) pyrrhogaster [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Histological analysis has shown that the bichir renal corpuscle has the same structure as both lungfish and freshwater teleosts and amphibians [ 12 , 13 , 14 , 15 ]. It has been established that the cut diameter of the renal corpuscle increases in the series P. senegalus —freshwater bony fish Ctenopharyngodon idella ; Channa punctatus —amphibians Rana cancrivora; Triturus (Cynops) pyrrhogaster [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the outer diameter of the tubules increases in the series P. senegalus —freshwater bony fish C. idella , C. punctatus —lungfish Protopterus dolloi—amphibians R. cancrivora, T. (Cynops) pyrrhogaster [ 12 , 13 , 15 , 16 ]. It is known that the outer diameter of the tubules depends both on the lumen of the tubules and on the height of the epitheliocytes that form the tubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sections were examined and photographed using a JEM −2,100 transmission electron microscope (JEOL Ltd., Tokyo, Japan). Whenever needed, the Adobe Photoshop CS6 software was used to enhance the visual contrast of the electron micrographs (Mokhtar, 2020; Soliman, Kamal, & Abd‐Elhafeez, 2019).…”
Section: Methodsmentioning
confidence: 99%